Prediction of combination therapies based on topological modeling of the immune signaling network in multiple sclerosis - Bernardo Faura, Martí; Rinas, Melanie; Wirbel, Jakob; Pertsovskaya, Inna; Pliaka, Vicky; Messinis, Dimitris E.; Vila, Gemma; Sakellaropoulos, Theodore; Faigle, Wolfgang; Stridh, Pernilla; Behrens, Janina R.; Olsson, Tomas; et al. (Genome medicine, 2021)
Multiple sclerosis (MS) is a major health problem, leading to a significant disability and patient suffering. Although chronic activation of the immune system is a hallmark of the disease, its pathogenesis is poorly understood, while current treatments only ameliorate the disease and may produce severe side effects.